Solid waste management: a study on the sanitary landfill (Bukit Tagar & Jeram sanitary landfill) / Mohd Zahiruddin Nordin - Nordin, Mohd Zahiruddin (2008)
A landfill, or also known as a dump or a tip, is a site for the disposal of waste materials by burial and is the oldest form of waste treatment. Historically, landfills have been the most common methods of organized waste disposal in many places around the world. Many landfills are also used for other waste management purposes, such as the temporary storage, consolidation and transfer, or processing of waste material in example sorting, treatment or recycling.